A Developmental Neuroscience Study of Moral Decision Making Regarding Resource Allocation. Issue 4 (16th December 2016) - Meidenbauer, Kimberly L.; Cowell, Jason M.; Killen, Melanie; Decety, Jean
Abstract : Distinguishing between equity and equality is essential when making social and moral decisions, yet the related neurodevelopmental processes are unknown. Evaluations of contextually based third‐party distributions incorporating recipient need and resource importance were examined in children and adolescents ( N =  82; 8–16 years). Spatiotemporal neurodynamic responses show distinct developmental profiles to viewing such distributions. Event‐related potentials (ERPs) differentially predicted real‐life behaviors based on age, where older children's (8–10 years) evaluations were related to a fairly rapid, automatic ERP component (early posterior negativity), whereas adolescent and preadolescent (11–16 years) evaluations, first‐person allocations, and prosocial behaviors were predicted by later, cognitively controlled ERP components (P3 and late positive potential). Together, these results reveal age‐related changes regarding the neural responses that correspond to distributive justice decisions.